2020
DOI: 10.1186/s12905-020-01012-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and the prevalence of urinary incontinence after surgical treatment for gynecologic cancer: a questionnaire survey

Abstract: Background: Although there have been a number of reports on urinary voiding symptoms associated with surgical interventions for gynecologic cancer and post-voiding symptoms, there have been few reports on urinary storage symptoms such as urinary incontinence (UI) and overactive bladder (OAB). The purpose of this study was to examine the rates and impact on quality of life (QOL) of urinary storage symptoms after gynecologic cancer surgery. Methods: A questionnaire survey, including Japanese-language versions of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Additionally, in women, the prevalence of urinary symptoms (OAB, urinary incontinence) is high in breast cancer patients treated with oral hormone therapy [ 144 ]. Moreover, urinary incontinence and OAB rates were found to be higher after gynecologic cancer surgery than in the general female population [ 145 ]. For these different reasons, the use of Rac1 inhibitors in cancer-associated bladder pathologies would make sense.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in women, the prevalence of urinary symptoms (OAB, urinary incontinence) is high in breast cancer patients treated with oral hormone therapy [ 144 ]. Moreover, urinary incontinence and OAB rates were found to be higher after gynecologic cancer surgery than in the general female population [ 145 ]. For these different reasons, the use of Rac1 inhibitors in cancer-associated bladder pathologies would make sense.…”
Section: Discussionmentioning
confidence: 99%
“…The caffeine content in tea, approximately one-third of that in coffee, prompted the exploration of other components potentially associated with lower urinary tract dysfunction [ 34 , 43 ]. Prior pelvic surgery is associated with higher ICIQ-UI scores, indicating a greater impact on QoL, possibly through structural or functional changes in the pelvic region [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lukacz et al [ 21 ] showed that childbearing leads to an increase in UI; Noriko Nakayama et al [ 22 ] observed multiple c-sections as a risk factor for UI after surgical treatment of gynecologic CA. However, both childbearing and c-section could not be shown as factors that impacted the ICIQ score in our study.…”
Section: Discussionmentioning
confidence: 99%